Bioactivity of Torch Ginger Umbut Extract (Etlingera elatior) Against Heal Wounds of Mice (Mus musculus) - Mhd Zalil Efendi; Ramadhan Sumarmin; M. Syukri Fadil (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2020)
Torch ginger has a wide range of good antimicrobial, antioxidant, anticancer, larvicidal and repellent activities. Active compounds in Torch ginger that affect pharmacological activities are phenols, polyphenols, flavonoids, and terpenoids. Based on these ingredients Torch ginger can be used to heal wounds. This study aims to observe the effect of Torch ginger Umbut extract on wound healing in mice. This study hopes to add information about the effect of Torch ginger umbut extract on the healing of cuts in mice so that it can be another alternative for wound healing and can be a reference for other researchers. This study used a completely randomized design with 5 treatments and 3 replications. Tests carried out on adult male mice. The results showed that the optimal wound healing in P2 is treatment with 10% Torch ginger umbut extract which requires a range of wound healing 7-8 days. Based on these results, Torch ginger umbut extract can heal wounds.